Mimesis: A Protean Concept - Wolf, Philipp (Journal of modern literature, 2024)
Homo Mimeticus is a transdisciplinary study that includes findings from philosophy, psychology, the arts (especially dramatics), politics, and the natural sciences, particularly neuroscience. Its reference horizon ranges from Plato’s idealist criticism of mimesis to Nietzsche’s "gay science," and Derrida’s deconstructive approach to Jane Bennett’s new materialism. Lawtoo goes far beyond the traditional version of mimesis as realist representation. He moves on from the structuralist and Freudian conceptions of René Girard and proposes, instead, a "mimetic re-turn" to a pre-Freudian psychology that encompasses a wide spectrum of unconscious and physiological pathos. These take effect on an intersubjective level and, due to modern mass communication, often develop pathological dimensions. Relational, dynamic, and supplementary as mimetic pathos is, it defies the stabilizing logic of original and copy, sameness and difference. Yet even though mimetic object and subject are inextricably intertwined, because of its intersubjectivity, pathos may also be reflectively countered and mediated from a distance, that is, an anti-mimetic patho-logy.